The Fractional Maximal Operator and Marcinkiewicz Integrals Associated with Schrödinger Operators on Morrey Spaces with Variable Exponent (Analysis in Theory and Applications, 2017)
In this paper, we prove the boundedness of the fractional maximal operator, Hardy-Littlewood maximal operator and marcinkiewicz integrals associated with Schrödinger operator on Morrey spaces with variable exponent.
Keywords: Fractional maximal operator; Marcinkiewicz integrals; Schrödinger; variable exponent; Morrey space.